Keluarga bahagia dalam islam Mahmud Ash-Shabbagh ; penerjemah Yudian Wahyudi Asmin ; Zaenal Muhtadin, Sarjana - ASH-SHABRAGH, Mahmud; Sarjana; Muhtadin, Zaenal; Asmin, Yudian Wahyudi (Pustaka Mantiq, 1993)
239 hlm 19 cm